Nuevos registros de Coccinellidae para el estado de Morelos, México - Trejo-Loyo, Adriana Gabriela; Nestor Arriola, Jorge Ismael (Instituto de Ecología, A.C., 2012)
We present three new records of lady beetles (Coccinellidae) from Central Mexico (Morelos): Paraneda pallidula guticollis, Anatis hydropica and Rodolia cardinalis. The first two are neotropical species and the last one is from Australia